Multi-state polarization switching and multifunction-integrated terahertz metadevice enabled by inverse resonance responses - Deng, Yuwang; Zhou, Qingli; Zhang, Xuteng; Zhang, Pujing; Liang, Wanlin; Ning, Tingyin; Shi, Yulei; Zhang, Cunlin (Frontiers in Physics, 2023)
Dynamical control of terahertz metadevices and integration of versatile functions are highly desired due to the increasing practical demands. Here, we propose a multifunctional photosensitive-Si hybrid metastructure consisting of twisted split-ring resonator pairs that could empower multi-state polarization switching and object-recognized imaging. The theoretical and simulated results show that inverse complete modulation of cross-polarized components could be realized via tuning the conductivity of Si-bridge. The calculated ellipticity indicates that our metadevices possess the abilities to convert linearly polarized (LP) light into left-hand circular-polarized (LCP) or right-hand circularpolarized (RCP) waves, as well as LCP or RCP into LP states. Combined with these properties, monoparameter amplitude imaging and amplitude-phase synergistic encryption imaging are accomplished. Our research provides a new strategy to develop reconfigurable and multifunctional components in terahertz regime.